The Role of Digital Technology in the Design of Mathematics Teaching and Learning: A Systematic Literature Review - Fitriana, Laila; Hendriyanto, Agus; Sahara, Sani; Muhaimin, Lukman Hakim; Wintarti, Atik; Listiawan, Tomi; Saputro, Anip Dwi; A Dewi, Deshinta (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study systematically reviews the role of digital technologies in the design of mathematics teaching and learning over the past decade. It aims to evaluate how digital tools have been integrated into task and lesson design, identifying emerging trends, challenges, and innovations. Methodology: A systematic literature review (SLR) following the PRISMA framework was conducted, analyzing studies published between 2014 and 2023. A total of 32 studies were included, sourced from various academic databases. These studies were examined to explore the use of digital technologies such as GeoGebra, Dynamic Geometry Environments (DGE), mobile apps, and others in mathematics instruction. Main Findings: The review found that digital technologies, particularly GeoGebra and DGE, were frequently used to enhance mathematical exploration and conjecturing. Other tools, including mobile applications, augmented reality (AR), and AI, have contributed to innovative teaching strategies, increasing student engagement and understanding. However, challenges such as unequal access to technology and the need for teacher training in tool integration were identified. Novelty/Originality of this study: This study provides a unique contribution by focusing not only on the use of digital tools but also on their role within the broader teaching design context. It offers insights into how these technologies shape pedagogical strategies, helping educators design more effective and inclusive mathematics education environments.